Effects of COVID-19 on Secondary Education in Uganda - Namara, Susan; Turyamureeba , Silaji; Eze, Chidinma Esther; Eze, Val Hyginus Udoka (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
The study aimed to examine the impact of COVID-19 on secondary education. It utilized a cross-sectional survey design, incorporating qualitative and quantitative methods. The research targeted 2 head teachers, 10 teachers, 36 students, and 7 parents, totaling 55 participants. The sample size of 80 respondents was determined using the solvens formula, comprising 4 head teachers, 24 teachers, 30 students, and 22 parents. Descriptive statistics were employed to analyze the data, with results presented through frequency counts and percentages. According to the study's findings, respondents noted that students received educational materials for home use, signifying that learning persisted through the home packages disseminated by schools during the COVID-19 period. The study ultimately concluded that delegating classroom operations and curriculum decisions to the community is a strategy to enhance the education system, improve teacher standards, and promote a school community for all students. Based on the findings, it was advised that adjustments be made at all education levels to adopt new strategies ensuring a continuous education process that is accessible, affordable, and flexible. Steps should be taken to prevent and address any disruptions in the education system, guaranteeing an uninterrupted flow of education